The Effect Of Solidification On The Microstructure And Mechanical Properties Of Modified Ductile Ni-Resist Iron With A High Manganese Content - Rashidi, M. M.; Mohd Hasbullah, Idris (Elsevier, 2014)
In this study, ductile Ni-resist with a minimum of 18 wt. % nickel composition was modified. Up to 12 wt. % manganese was added together with 10 wt. % nickel to investigate the effects of the alloying elements on its solidification, microstructure and mechanical properties. Effect of solidification stage on the primary dendrite arm spacing (DAS), secondary dendrite arm spacing (SDAS), graphite aggregate, carbide and series of mechanical properties were evaluated. Results show that DAS, SDAS, graphite aggregate and carbide are directly dependent on the solidification-cooling rate. Consequently, a series of mechanical properties affected as well. A tensile strength of modified ductile Ni-resist is decrease with higher manganese content.